CCTα and CCTδ chaperonin subunits are essential and required for cilia assembly and maintenance in Tetrahymena - Seixas, Cecília (2010)
Background - The eukaryotic cytosolic chaperonin CCT is a hetero-oligomeric complex formed by two rings connected back-to-back, each composed of eight distinct subunits (CCTalpha to CCTzeta). CCT complex mediates the folding, of a wide range of newly synthesised proteins including tubulin (alpha, beta and gamma) and actin, as quantitatively major substrates. Methodology/Principal findings - We disrupted the genes encoding CCTalpha and CCTdelta subunits in the ciliate Tetrahymena. Cells lacking the zygotic expression of either CCTalpha or CCTdelta showed a loss of cell body microtubules, failed to assemble new cilia and died within 2 cell cycles. We also show that loss of CCT subunit activity leads to axoneme shortening and splaying of tips of axonemal microtubules. An epitope-tagged CCTalpha rescued the gene knockout phenotype and localized primarily to the tips of cilia. A mutation in CCTalpha, G346E, at a residue also present in the related protein implicated in the Bardet Biedel Syndrome, BBS6, also caused defects in cilia and impaired CCTalpha localization in cilia. Conclusions/Significance - Our results demonstrate that the CCT subunits are essential and required for ciliary assembly and maintenance of axoneme structure, especially at the tips of cilia.